Analisis Pengembangan Kawasan Pesisir Sebagai Zona Konservasi Mangrove Wonorejo Surabaya - Suning, Suning; Dwika Aditya Ananta (Universitas Dr. Soetomo, 2024)
The Wonorejo Surabaya Mangrove Forest is located on the coast of Rungkut District and has an area of ​​36.9 Ha. The potential can be developed as a tourism-based ecosystem. The potential and existing problems are empirically related to the provision of public facilities, the need to rejuvenate tourist facilities, the need for tourism development, and the need to improve water environmental management. The aim of this research is to determine the existing conditions and the strategy for developing the Wonorejo Mangrove coast as a conservation zone. The research method used is descriptive qualitative with photo mapping techniques and SWOT analysis. The research results show that the existing condition of the Wonorejo Mangrove coast has a built-up land use of 14% and non-built land use of 86%. There are circulation facilities for two-wheeled and four-wheeled vehicles as one of the facilities for visitors. Availability of green open space in the form of playgrounds and other green open space spots such as parking areas for both two-wheeled and four-wheeled vehicles. The characteristics of existing buildings include roof shape, building texture and paint color. The tourist support facilities that are available are boat rides, playgrounds, toilets, entrance counters, culinary centers, information centers and research facilities on mangroves. Physically, the pedestrian path has a paving construction with a width of 4 m and a length of 18 m, as well as a jogging track area with a wooden construction with a width of 2 m and a length of 1,217 m. Signage is in the form of directional signs, directional signs and warning boards, as well as existing conservation in the form of mangrove and boesem areas. Policy implementation that can be carried out is the need to develop mangrove conservation and rehabilitation activities as tourism and research programs, repair and maintenance of supporting facilities, signage, pedestrian paths, enforce laws and regulations related to conservation areas, develop synergistic and sustainable waste management with industries such as PT. Unilever and parties who care about mangrove and environmental issues in order to maintain the sustainability of the Wonorejo Mangrove.